50. CURRENT STATE OF HEALTHCARE WORKERS' ATTITUDES TOWARDS PATIENT SAFETY AT VINH THUAN DISTRICT MEDICAL CENTER, KIEN GIANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: Description of the current state of healthcare workers' attitudes towards patient safety at Vinh Thuan district Medical Center in 2024.Subjects and methods: Cross-sectional descriptive study of 60 medical staff currently working at clinical departments of Vinh Thuan district Medical Center.Results and conclusions: The overall patient safety attitude at Vinh Thuan district Medical Center was as positive safety, which includes 6 factors, the highest being teamwork environment, job satisfaction, and hospital management, with scores of 4.2 ± 0.3 poits; 4.2 ± 0.4 poits; and 4.2 ± 0.4 poits, respectively - all was classified as positive safety. The contents of safety environment and working conditions achieved an average score of 4.1 ± 0.3 points and 4.1 ± 0.4 points, respectively - both classified as positive safety. The lowest score was for work pressure, with an average of 3.8 ± 0.6 poits, indicating a less positive safety attitude.
Keywords: Medical staff; patient safety; Vinh Thuan district Medical Center.